2020
DOI: 10.1101/2020.09.17.300863
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Thalamus and claustrum control parallel layer 1 circuits in retrosplenial cortex

Abstract: The granular retrosplenial cortex (RSG) is critical for both spatial navigation and fear conditioning, but the neural codes enabling these seemingly disparate functions remain unknown. Here, using optogenetic circuit mapping, we reveal a double dissociation that allows parallel circuits in superficial RSG to process navigation- versus fear-related inputs. The anterior thalamus, a source of head direction information, strongly recruits small, low rheobase (LR) pyramidal cells in RSG layer 3. Neighboring regular… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 150 publications
(290 reference statements)
3
32
0
Order By: Relevance
“…Our single neuron tracing data are much better than the bulk tracing technique to identify the laminar distribution of their cortical targets without contamination. Different laminar distributions between claustrocortical projections and thalamocortical projections influence different cell types in the cortex (Brennan et al, 2021). It may be underly the mechanisms that neuron responses differ in cortical areas, layers and cell types after optical activating the CLA neurons (McBride et al, 2022)…”
Section: Discussionmentioning
confidence: 99%
“…Our single neuron tracing data are much better than the bulk tracing technique to identify the laminar distribution of their cortical targets without contamination. Different laminar distributions between claustrocortical projections and thalamocortical projections influence different cell types in the cortex (Brennan et al, 2021). It may be underly the mechanisms that neuron responses differ in cortical areas, layers and cell types after optical activating the CLA neurons (McBride et al, 2022)…”
Section: Discussionmentioning
confidence: 99%
“…Yet again, despite reports of head direction cells (Jankowski et al, 2015;Tsanov et al, 2011), AHV-tuned neurons have not been reported in these thalamic structures. Interestingly, recent modeling data suggest that synaptic dynamics of anterior thalamic inputs to the RSP may transform the head direction input to angular speed signal (Brennan et al, 2021). Alternatively, the laterodorsal thalamus, which receives direct afferents from the medial vestibular nucleus (Shiroyama et al, 1999) could be a source of AHV information.…”
Section: Articlementioning
confidence: 99%
“…Another study also recorded in PFC but used different, prolonged CLA optogenetic stimulation patterns and found that a majority of frontal neurons increased in firing rate, rather than decreased (Fodoulian et al, 2020). In addition, a recent slice physiology study found that stimulation of CLA axons drove robust excitatory post-synaptic potentials in RSP pyramidal neurons (Brennan et al, 2021). Thus, the nature of CLA's influence on cortex remains unresolved.…”
Section: Introductionmentioning
confidence: 99%